2010
DOI: 10.1074/jbc.m110.141119
|View full text |Cite
|
Sign up to set email alerts
|

Association with β-COP Regulates the Trafficking of the Newly Synthesized Na,K-ATPase*

Abstract: Plasma membrane expression of the Na,K-ATPase requires assembly of its ␣-and ␤-subunits. Using a novel labeling technique to identify Na,K-ATPase partner proteins, we detected an interaction between the Na,K-ATPase ␣-subunit and the coat protein, ␤-COP, a component of the COP-I complex. When expressed in the absence of the Na,K-ATPase ␤-subunit, the Na,K-ATPase ␣-subunit interacts with ␤-COP, is retained in the endoplasmic reticulum, and is targeted for degradation. In the presence of the Na,K-ATPase ␤-subunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
(25 reference statements)
1
10
0
Order By: Relevance
“…To test if this region is involved in setting the differential localization, a set of chimeras with this region exchanged were analyzed. GFP‐α3 /α4 and GFP‐α4 /α3, were localized in patterns opposite to that of the parent constructs demonstrating that the targeting information lies within the intrinsically disordered region (Figure A,B). A subsequent pair of chimeras with only 24 amino acids substituted, GFP‐α3 /α4 and GFP‐α4 /α3, was generated and found to also have reversed localization patterns compared with the parent constructs (Figure C,D).…”
Section: Resultsmentioning
confidence: 96%
“…To test if this region is involved in setting the differential localization, a set of chimeras with this region exchanged were analyzed. GFP‐α3 /α4 and GFP‐α4 /α3, were localized in patterns opposite to that of the parent constructs demonstrating that the targeting information lies within the intrinsically disordered region (Figure A,B). A subsequent pair of chimeras with only 24 amino acids substituted, GFP‐α3 /α4 and GFP‐α4 /α3, was generated and found to also have reversed localization patterns compared with the parent constructs (Figure C,D).…”
Section: Resultsmentioning
confidence: 96%
“…Using APP biotinylation assays, we previously showed that δ-COP silencing dramatically decreased the amount of APP at the cell surface (3). Here we demonstrated that this effect was relatively specific for APP as the amount of Notch [gammasecretase substrate that has a half-life comparable to APP (10,11)], two other cargo proteins of the COPI complex (NMDAR and Na,K-ATPase) (12,13), as well as two resident proteins of the cell surface (E-cadherin and syndecan) were unchanged ( Fig. 1 E and F).…”
Section: Significancementioning
confidence: 82%
“…Recently, it has been shown in COS cells that the Na pump asubunit physically interacts with b-coatomer protein (b-COP) shortly after translation and threading into the ER, and is targeted for degradation (Morton et al, 2010). In order to 'rescue' the asubunit from ER degradation, its interactions with b-COP must be replaced with an association between the Na pump a-and bsubunits (Morton et al, 2010).…”
Section: Namentioning
confidence: 99%
“…Recently, it has been shown in COS cells that the Na pump asubunit physically interacts with b-coatomer protein (b-COP) shortly after translation and threading into the ER, and is targeted for degradation (Morton et al, 2010). In order to 'rescue' the asubunit from ER degradation, its interactions with b-COP must be replaced with an association between the Na pump a-and bsubunits (Morton et al, 2010). Interestingly, we observed that not only was a-b assembly required for proper trafficking of the complex, but that assembly immediately produced a significant ouabain-sensitive Na pump in ER microsomes (Gatto et al, 2001).…”
Section: Namentioning
confidence: 99%